Republic of Kazakhstan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2010)
Kazakhstani banks continue to suffer from a high and rising stock of nonperforming loans. A centralized approach to asset resolution is warranted, and could be based on a reinvigorated Distressed Asset Fund. A robust and transparent public financial management system should be an integral part of any effective fiscal framework. Deeper and sophisticated domestic financial markets will help decline in dollarization and the associated risks. A sound medium-term fiscal framework, supportive monetary and exchange rate policies, and overall financial sector reform is required.